Analysis of Pay Later Payment System on Online Shopping in Indonesia - Yeyen Pratika; Salahudin Salahudin; Dicky Wisnu Usdek Riyanto; Titiek Ambarwati (Universitas Hayam Wuruk Perbanas, 2020)
Due to the technology development, the digital payment is becoming more attractive to consumers. This type of payments provides an easy way for consumers to meet their needs. Pay later is currently one of the most attractive digital payments in Indonesia. This system, which is similar to credit card, allows consumers to buy products or services with the possibility to pay them later. This study aims to examine the pay later system and the consequences of applying it in Indonesian market. This study used a qualitative approach using online news content analysis to understand the issue of pay later. The software used in this study is Nvivo plus 12 by utilizing the word similarity, cluster analysis and matrix coding functions. The results show that pay later has a correlation with credit due to the system allows consumers to pay in installments. In addition, this pay later provides a possibility of impulsive buying for consumers. However, this study is limited to analysis based on online news data. It suggests that future studies combine online news with interviews or observation or many others documents to get a more comprehensive result.